The Three Nociceptive Responses of the Orbicularis Oculi Reflex in Alzheimer's Disease: State of the Evidence and Meta-analysis. (September 2019) - Leon-Ariza, Juan S.; Prada, Diddier G.; Leon-Ariza, Daniel S.; Castillo, Camilo; Leon-Sarmiento, Fidias E.
There is an emerging belief that electrically elicited blink reflexes (BR) may distinguish Alzheimer's disease (AD) from other disorders characterized by memory dysfunction. To qualitatively and quantitatively distinguish the effects that electrical stimulation has over the blink reflex (eBR) recorded from patients with AD and healthy controls (HCs), we did a systematic review of the literature, and conducted a meta-analysis. Following our selected criteria, 94 AD patients and 97 HCs were identified from articles published in English between 1950 and 2017. Although the 3 responses (R1, R2 and R3) of the eBR were studied in a number of patients, only the R2 response was quantified in all studies. Thresholds and stimulation intensities parameters were found to be used in a miscellaneous form, and the majority of times, such parameters deviated from validated guidelines. The stimulation frequencies used to elicit the BR responses ranged between 0.14 and 0.2 Hz. These frequencies favored HCs compared with AD patients (odds ratio = 1.08; 95% CI = 0.30-1.85), I 2 = 0% [ P = .99]; Q = 271.89 [ df = 7, P < .000]). Egger's regression test suggested publication bias (intercept = 32.38; 95% CI = −8.98 to −3.2; P = .001). Our results unveiled key shortcomings in the data reported; such shortcomings need to be corrected in future AD research looking for obtaining more reliable and reproducible eBR studies; otherwise, interventions may be misleading.